1997
DOI: 10.1071/pc970275
|View full text |Cite
|
Sign up to set email alerts
|

Use by birds of riparian vegetation in an extensively fragmented landscape

Abstract: The bird communities of six riparian woodland sites are described and compared with those of eight terrestrial woodland sites in the Central Tablelands near Bathurst, New South Wales, Australia. Riparian woodland, where still present in the Central Tablelands, is dominated by either relatively narrow strips of Casuarina cunninghamiana along stream banks or the less restricted Angophora floribunda trees associated with Eucalyptus melliodora?E. blakelyi woodlands. Four of the riparian sites were located within c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…Loss of these plant species and their associated structural elements is likely to result in very significant changes in movement and foraging ability. Other studies similarly highlight the importance of canopy trees in the matrix (Munyenyembe et al 1989;Law et al 2000;Grabham and Klomp 2001) and in remnants with most bird species being observed in the tree canopy of riparian remnants (Fisher 1997), and along a regeneration gradient (Fisher 2001).…”
Section: Discussionmentioning
confidence: 89%
“…Loss of these plant species and their associated structural elements is likely to result in very significant changes in movement and foraging ability. Other studies similarly highlight the importance of canopy trees in the matrix (Munyenyembe et al 1989;Law et al 2000;Grabham and Klomp 2001) and in remnants with most bird species being observed in the tree canopy of riparian remnants (Fisher 1997), and along a regeneration gradient (Fisher 2001).…”
Section: Discussionmentioning
confidence: 89%
“…Floodplains and riparian zones are host to a wide range of woodland bird species that also occur in non-floodplain communities (Appendix 1; Fisher and Goldney 1997;Major et al 2001;Antos and Bennett 2005). These include resident, nomadic, and migratory groups, and many threatened and declining species (Reid and Fleming 1992;Reid 1999).…”
Section: Floodplain Woodland Birdsspecies Composition and General Habmentioning
confidence: 99%
“…Woodland bird species richness, diversity, abundance, density, and breeding numbers have all been demonstrated to be significantly greater in floodplains and riparian zones compared with 'dry' non-floodplain and agricultural environments in Australia and the USA (Stauffer and Best 1980;Szaro and Jakle 1985;Best et al 1995;Fisher and Goldney 1997;Woinarski et al 2000). How different floodplain and riparian communities are from adjacent communities varies depending on scale, but in general differences in vegetation and bird communities between these environments are more distinct in rangelands and broadacre agricultural zones (Szaro and Jakle 1985;Knopf and Samson 1994;Saab 1999).…”
Section: Floodplain Woodland Birdsspecies Composition and General Habmentioning
confidence: 99%
“…The juxtaposition of two dissimilar habitats increased habitat heterogeneity and provided resources for the most diverse assemblage of birds, a combination of forestand woodland-dependent species, and a larger number of opencountry foragers that have benefited from land-clearing (Fisher and Goldney, 1997). Riparian zones including gullies are characterised by higher moisture and nutrient levels than dryland, with increased structural complexity and elevated productivity, even in gullies without permanent water (Mac Nally et al, 2000), which in turn attracts species in greater densities (Bentley and Catterall, 1997;Woinarski et al, 2000;Palmer and Bennett, 2006).…”
Section: Species Richness and Abundance Of Forests Plantations And mentioning
confidence: 99%
“…The placement and management of these plantations will have significant effects on the biota within or around them. Moreover, remnants within plantations, such as riparian corridors which are known to support greater productivity and higher species richness and abundance (Bentley and Catterall, 1997;Fisher and Goldney, 1997), may provide linkages that assist dispersal and colonisation (Nasi et al, 2008), important functions given the highly fragmented nature of the reserve system. It is therefore important to assess the effectiveness of these remnants as linkages, when buffered by plantations.…”
Section: Introductionmentioning
confidence: 99%